Financial Inclusion of Islamic Banking and Financial Technology as a Growth Factor for MSMEs - Jannah, Annisa Maftuhatul; Budiarti*, Isniar (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
This study discusses issues that occur in MSMEs that have difficulties and low levels of access for MSMEs owners to banking services in the sharia sector and the use of Financial Technology in financial institutions, aims to examine the effect of Islamic banking financial inclusion, the use of Financial Technology on the growth of MSMEs in the region Bandung. The method used is descriptive and verification with a quantitative approach, by distributing questionnaires to 90 MSMEs owners assisted by Kadin West Java, analyzed using multiple linear regression analysis techniques with the IBM SPSS 26.0.0 Software program. The results of the study show that the Financial Inclusion of Islamic Banking and Financial Technology has a high effect on MSME growth. The impact of this research is to provide information and advice to MSMEs because with access to Islamic banking financial inclusion and the use of fintech by MSMEs themselves can increase the growth of MSMEs. Keywords: Islamic Banking Financial Inclusion; Financial Technology; MSMEs Growth; Banking Economy; MSMEs Conditions Penelitian ini membahas isu yang terjadi pada kesulitan UMKM dan rendahnya akses UMKM pada layanan perbankan di sektor syariah dan penggunaan teknologi keuangan pada lembaga keuangan, bertujuan untuk menguji pengaruh inklusi keuangan perbankan syariah, penggunaan teknologi keuangan terhadap pertumbuhan UMKM yang berada di wilayah Kota Bandung. Metode yang digunakan adalah deskriptif dan verifikatif dengan pendekatan kuantitatif, melalui penyebaran kuesioner kepada 90 pemilik UMKM binaan Kamar Dagang dan Industri (Kadin) Provinsi Jawa Barat, dianalisis menggunakan teknik analisis regresi linear berganda. Hasil penelitian menunjukan bahwa Inklusi Keuangan Perbankan Syariah dan teknologi keuangan berpengaruh tinggi terhadap Pertumbuhan UMKM. Dampak dari penelitian ini memberikan informasi dan saran kepada pelaku UMKM karena dengan adanya akses dari inklusi keuangan perbankan syariah dan penggunaan fintech oleh UMKM itu sendiri dapat meningkatkan pertumbuhan UMKM. Kata Kunci: Inklusi Keuangan Perbankan Syariah; Teknologi Keuangan; Pertumbuhan UMKM; Ekonomi Perbankan; Kondisi UMKM